Climate Change Spillover Effects on Agricultural Economics: Correlating Rainfall Anomalies (ENSO) and Farmer's Terms of Trade in Indonesia - Leni Sabrina; Nurhapsa Nurhapsa; Elly Jumiati (Agriculture Journal, 2026)
This study investigates the profound socioeconomic implications of precipitation variability on agricultural stability, specifically focusing on how ENSO-induced rainfall anomalies trigger economic spillover effects within the Indonesian agrarian sector. Addressing the critical intersection of climatology and macroeconomics, the research aims to quantify the correlation between meteorological shocks and the Farmer's Terms of Trade (FTT). Utilizing official secondary datasets from the Bureau of Meteorology, Climatology, and Geophysics (BMKG) and Statistics Indonesia (BPS) for the period 2021–2024, the study employs a quantitative approach integrating Pearson correlation analysis and the Vector Error Correction Model (VECM). The results demonstrate a significant positive correlation (r = .658 ; p = .003) between rainfall stability and farmer welfare, revealing a severe "price-squeeze" effect during the 2023 El Niño where escalating production costs outpaced commodity gate prices. Furthermore, the findings highlight that technical irrigation infrastructure acts as a vital moderator, significantly dampening economic volatility in resilient provinces like South Sulawesi compared to rain-fed regions. We conclude that climate-driven economic erosion necessitates a transition toward proactive policy frameworks, such as Weather Index-Based Insurance (WIBI), to safeguard rural purchasing power. This research advances scientific knowledge by empirically decoupling the physical impacts of climate change from its structural economic consequences in tropical agriculture.